Thorax Photo Analysis Of Covid 19 Patients In West Java Province Mental Hospital - Kiagus Roy (Sean Institute, 2023)
The Corona Virus or commonly called Covid 19 began to spread and shocked the world at the end of 2019. And entered Indonesia in early 2020 with various clinical symptoms that appeared. Starting from a mild cough, fever with high temperatures, shortness of breath to pneumonia and respiratory failure. Symptoms of the Covid 19 virus are categorized into 4 aspects consisting of mild, moderate, severe to critical symptoms. One way to diagnose a patient with the corona virus is to do a chest X-ray. This is one of the diagnoses that is carried out as a preventive way to evaluate the airway, lung parenchyma to blood vessels and heart. In addition to evaluating the pleura, mediastinum and also the chest wall. This research was carried out using a qualitative method with a literature review approach to patients at the West Java Provincial Mental Hospital. This research was conducted at the West Java Province Psychiatric Hospital and found a relationship between clinical symptoms and chest photo images of Covid 19 patients at the West Java Mental Hospital.